KAJIAN PEMBERIAN BERAGAM DOSIS PUPUK NPK MUTIARA TERHADAP RESPONS AGRONOMIS TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Muhammad Noor Ariefin; Antoni Eduard De Monford Pratama, Mario; Rofita, Dewi; Knaofmone, Elfrida; Adiputra Taopan, Rizki; Angelina Simanjuntak, Nella; Priskilla Purba, Dumaris (Agriculture, 2025)
Sweet corn is a horticultural commodity with high economic value and increasing market demand. The appropriate application of NPK fertilizer greatly affects plant growth and yield. This study aims to determine the effect and optimum dosage of Mutiara NPK fertilizer on the growth and yield of sweet corn plants. This study was conducted in Golo Dukal Village, Langke Rembong District, Manggarai Regency, East Nusa Tenggara, from March 2025 to June 2025. The method used in this study was a randomized block design (RAK) consisting of 5 treatments repeated 5 times. The treatments used were as follows: N0: 0 kg/ha (0 g/bed), N1: 100 kg/ha NPK (2.5 g/bed), N2: 200 kg/ha NPK (5 g/bed), N3: 300 kg/ha NPK (7.5 g/bed), N4: 400 kg/ha NPK (8 g/bed). The total number of treatments was 25 beds, with each experimental unit containing 10 plants and 3 sample plants, resulting in a total of 5 x 5 x 10 = 250 plants. Based on the research results, it can be concluded that the application of various doses of Mutiara NPK fertilizer has a significant effect on all growth parameters and sweet corn yields. The Mutiara NPK fertilizer dose treatment N2: 200 kg/ha NPK (5 g/bed) is the most optimal dose for all observation parameters.